2021
DOI: 10.32598/jhnm.31.2.2089
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Caregivers of Patients Undergoing Hemodialysis

Abstract: Introduction: There is a scarcity of literature about the burden of hemodialysis patients’ caregivers. Caregivers often receive little attention, and the primary focus is always on the patients. Frequent hospitalizations and factors associated with the disease can lead to depression and reduce the caregiver’s quality of life. Objective: The study aimed to determine the burden of caregivers of patients undergoing hemodialysis at a tertiary care hospital. Materials and Methods: This cross-sectional analytical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
2
3
2
Order By: Relevance
“…The outbreak of COVID-19 has led to adverse economic, social, and health consequences in different countries (3). The results of the present study showed that physical care burden had the lowest score among other dimensions of care burden, which was inconsistent with the results of studies by Sanmar et al (40) and Sharma et al (41) suggesting that caregivers bore enormous psychological and physical burden. The inconsistency may have been due to the fact that very limited time is needed to care for patients with COVID-19, while a great deal of time and even years are required to care for dialysis patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The outbreak of COVID-19 has led to adverse economic, social, and health consequences in different countries (3). The results of the present study showed that physical care burden had the lowest score among other dimensions of care burden, which was inconsistent with the results of studies by Sanmar et al (40) and Sharma et al (41) suggesting that caregivers bore enormous psychological and physical burden. The inconsistency may have been due to the fact that very limited time is needed to care for patients with COVID-19, while a great deal of time and even years are required to care for dialysis patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the present research demonstrated that among five domains of FCB, physical caregiver burden in comparison to other aspects scored the lowest level. This result was inconsistent with the studies of [30][31][32]. These studies revealed that caregivers are exposed to a considerable degree of physical and mental pressure when caring for a patient.…”
Section: Discussioncontrasting
confidence: 70%
“…In this study, most subjects were middle-aged with a mean age of more than 40 years. This study also shows that there is no significant relationship between the level of burden scores and the selected sociodemographic variables of the participants (Sharma et al, 2021). This study also shows a similarity with the study results that some sociodemographics do not have a significant relationship with caregiver burden.…”
Section: Discussionsupporting
confidence: 79%
“…A similar study used the ZBI score with a sample ) families have a medium to a heavy burden, Families are light to moderately burdened because the average burden score is 25±12 (range 0-88) (Sharma et al, 2021). Caregiver burden (as measured by ZBI) increased significantly over time (p < 0.01), with mean scores at baseline in the light burden range and increasing to moderate burden 12 months later.…”
Section: Discussionmentioning
confidence: 99%